MEMPERKUAT KESIAPSIAGAAN MASYARAKAT DAN MITIGASI BENCANA TERHADAP ANCAMAN BENCANA GEMPA BUMI DI DESA SANTONG MULIA - Solikatun; Agustina, Rezqi Maulanda; Nirmala, Yulia; Ananda, Diaz Khalid; Aldino, Dhafin Rizky; Aulia, Putri; Adam, Aura Masitha; Rahmayani, Isty; Windiati; Taufaturrahman; Iwandaka, Age (Universitas Mataram, 2024)
Santong Mulia Village is one of 10 villages located in Kayangan District, North Lombok Regency which has a high risk of earthquake disasters. To face earthquake disasters, disaster preparedness and mitigation are needed. The method of activity carried out is conducting Focus Group Discussion (FGD) and socialization. Participants in community empowerment activities are the hamlet head of Santong Mulia village, the Village Disaster Preparedness Team (TSBD), BPD and the community. The activity was carried out on Tuesday 9 January 2024 at the Community Evacuation Center (PEM) building in Santong Mulia village. This activity aims to increase preparedness capacity and increase community participation in disaster mitigation, especially earthquakes. The result of this community empowerment activity is increased awareness and preparedness of the Santong Mulia Village Community regarding disaster mitigation. Activities that have been carried out include socialization regarding village disaster documents, destana development, inclusive disaster management and earthquake-resistant houses. The results of data processing from 10 respondents showed that before holding the socialization, 54% of the community already had knowledge about disaster preparedness and mitigation, while the other 46% did not have the knowledge. This happens because of the lack of education to the public regarding disaster preparedness and mitigation. After holding the outreach, the community's knowledge regarding disaster preparedness and mitigation changed to 100% of the community having knowledge about disasters and disaster mitigation. The relative growth results show an increase in public knowledge regarding disasters and disaster mitigation by 85.19%.